2023
DOI: 10.1017/s0033291723000685
|View full text |Cite
|
Sign up to set email alerts
|

Which psychotherapy is most effective and acceptable in the treatment of adults with a (sub)clinical borderline personality disorder? A systematic review and network meta-analysis

Abstract: A broad range of psychotherapies have been proposed and evaluated in the treatment of borderline personality disorder (BPD), but the question which specific type of psychotherapy is most effective remains unanswered. In this study, two network meta-analyses (NMAs) were conducted investigating the comparative effectiveness of psychotherapies on (1) BPD severity and (2) suicidal behaviour (combined rate). Study drop-out was included as a secondary outcome. Six databases were searched until 21 January 2022, inclu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
17
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 16 publications
(20 citation statements)
references
References 86 publications
(127 reference statements)
1
17
0
Order By: Relevance
“…There is no evidence that psychotherapy is associated with a higher rate of serious adverse events compared with TAU (risk ratio, RR=0.86, 95% CI: 0.14-5.09; n=4, N=571, p=0.86) 17 . Generic methods of psychotherapy (e.g., general psychiatric management, structured clinical management, client-centered therapy, supervised team management) were found to be inferior to specialized psychotherapies such as DBT, MBT or schema therapy 216 .…”
Section: Efficacy Of Psychotherapy In Bpdmentioning
confidence: 99%
See 2 more Smart Citations
“…There is no evidence that psychotherapy is associated with a higher rate of serious adverse events compared with TAU (risk ratio, RR=0.86, 95% CI: 0.14-5.09; n=4, N=571, p=0.86) 17 . Generic methods of psychotherapy (e.g., general psychiatric management, structured clinical management, client-centered therapy, supervised team management) were found to be inferior to specialized psychotherapies such as DBT, MBT or schema therapy 216 .…”
Section: Efficacy Of Psychotherapy In Bpdmentioning
confidence: 99%
“…Due to the limited number of RCTs, meta-analyses specifically focusing on between-group effect sizes with ST are not available 229 . The most recent meta-analysis on psychotherapy for BPD included only three RCTs of ST 216 . As noted above, in reducing BPD symptoms, ST was found to be superior to DBT and CBT, but not MBT or TFP 216 .…”
Section: Efficacy Of Psychotherapy In Bpdmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus there is good evidence for a number of methods that have somewhat different theoretical root, including dialectical behavior therapy (Linehan, 1993), mentalization-based treatment (Bateman and Fonagy, 2004), and transference-focused psychotherapy (Yeomans et al, 2002). Each of these methods has been supported by clinical trials, but no single therapy has been shown to be superior (Storebø et al, 2018; Setkowski et al, 2023), and all of these have an implicit or explicit adherence to a biopsychosocial model. This suggests that all effective treatments make use of common factors and may not be wholly dependent on underlying theories (Choi-Kain, 2020).…”
Section: Interactions Between Emotion Dysregulation and Invalidationmentioning
confidence: 99%
“…
Setkowski et al (2023) published an ambitious paper asking, 'Which psychotherapy is most effective…in the treatment of … borderline personality disorder?' They employ network meta-analysis (NMA), a statistical procedure that estimates the comparative effectiveness of interventions never trialed against each other, but against the same comparator, most often 'treatment as usual' (TAU), but also, other interventions that are better matched in dose, focus, and expertise with the treatments of interest.The authors enumerate limitations of their study responsibly, which include first and foremost the heterogeneity of control conditions in studies.
…”
mentioning
confidence: 99%